Modificación de la proteína SV2A durante la generación de la epilepsia y su asociación con la respuesta al levetiracetam - Contreras García, Itzel Jatziri (Universidad Autónoma Metropolitana, 2019)
Synaptic vesicle protein 2A (SV2A) has become an attractive target of investigation due to its possible role in the pathophysiology of epilepsy. This protein is expressed ubiquitously in all nerve terminals independently of their neurotransmitter content. A decrease in SV2A levels has been reported in patients with refractory epilepsy and in animal models of epilepsy. This reduction may be directly associated with the great variability in the response to treatment with levetiracetam, a drug that targets SV2A. Thus, the present study evaluated modifications in SV2A expression in the hippocampus of rats throughout the generation of epilepsy. The association between changes in this protein levels during late epilepsy and the response to the levetiracetam was also analyzed. A model of temporal lobe epilepsy induced with lithium-pilocarpine was used, since it resembles with high fidelity the changes observed in patients with this neurological disorder. Wistar male rats were treated with pilocarpine to induce status epilepticus (SE), which lasted 90 minutes; this group was sacrificed 1 hour after SE. Another two groups of rats (early and late epileptic) were kept under normal conditions after SE generation until their sacrifice. Both groups were video-monitored for 8:00 am to 6:00 pm to evaluate behavioral seizures; the early epileptic group was sacrificed on 10 day after the SE and the late epileptic group on day 56. To evaluate whether the effect of levetiracetam depends on SV2A levels, on another group the same procedure as for the late epileptic group was performed, but on day 49, osmotic pumps were implanted which released levetiracetam (260 mg/kg s.c.) for a week; they were sacrificed on day 56. The brain of all animals was obtained; SV2A protein expression was assessed by immunohistochemistry in 10 layers of the hippocampus. SV2A protein levels were increased mainly in somatic layers, associated with the GABAergic system during SE. In late epilepsy, SV2A protein levels increased in layers with axo-dendritic connections and no relationship to a particular neurotransmitter was found. On the other hand, after levetiracetam treatment the rats were divided into two groups, those that responded and those that did not. Although there was great variability in SV2A levels in late epilepsy, animals with lower SV2A immunoreactivity did not respond to treatment with the antiepileptic drug.; La proteína de vesícula sináptica 2A (SV2A) se ha convertido en un atractivo blanco de investigación debido a su posible papel en la fisiopatología de la epilepsia. Esta proteína se encuentra expresada de manera ubicua en todas las terminales nerviosas de manera independiente del neurotransmisor que contenga. En pacientes con epilepsia refractaria y en modelos animales de epilepsia se ha reportado una disminución en la inmunorreactividad de SV2A. Este decremento podría estar asociada directamente con la gran variabilidad en la respuesta al tratamiento con levetiracetam, un fármaco cuyo blanco es la SV2A.Por ello, el presente trabajo evaluó las modificaciones en la inmunorreactividad de SV2A en el hipocampo de ratas, a lo largo de la generación de la epilepsia. También se analizó la relación entre los cambios de la inmunorreactividad de la proteína durante la epilepsia tardía y la respuesta al fármaco levetiracetam. Por ello, se usó un modelo de epilepsia del lóbulo temporal inducida con litio-pilocarpina, debido a que semeja con alta fidelidad los cambios observados en pacientes con este desorden neurológico. Se administró pilocarpina a ratas macho para inducir status epilepticus (SE), el cual duró 90 minutos; este grupo fue sacrificado 1 hora posterior al SE. Otros grupos de ratas (epiléptico temprano y tardío) se mantuvieron en condiciones normales después de la generación del SE hasta su sacrificio. Estos grupos fueron video-monitoreados de 8:00 am a 6:00 pm para evaluar las crisis conductuales; el grupo epiléptico temprano se sacrificó el día 10 posterior al SE y el epiléptico tardío el día 56; en otro grupo se realizó el mismo procedimiento que para el grupo epiléptico tardío, pero en el día 49 se les implantó bombas osmóticas que liberaron levetiracetam (260 mg/kg s.c.) por una semana y se sacrificaron el día 56. Se obtuvo el cerebro de ratas y se evaluó la inmunorreactividad de SV2A por inmunohistoquímica en 10 capas del hipocampo. Se observó un aumento en la inmunorreactividad de SV2A asociado al sistema GABAérgico en capas principalmente somáticas durante el SE. En la epilepsia tardía la inmunorreactividad de SV2A aumentó en capas con conexiones axo-dendríticas y no hubo relación con algún neurotransmisor. Por otro lado, posterior al tratamiento con levetiracetam se dividieron las ratas en dos grupos, el responsivo y el no responsivo. Aunque se observó una gran variabilidad en los niveles de la SV2A durante la epilepsia tardía, los animales con menor inmunorreactividad de SV2A no respondieron al tratamiento con el fármaco antiepiléptico.